Abbreviated Antiplatelet Therapy in Patients at High Bleeding Risk With or Without Oral Anticoagulant Therapy After Coronary Stenting: An Open-Label, Randomized, Controlled Trial. Issue 15 (29th August 2021) - Smits, Pieter C.; Frigoli, Enrico; Tijssen, Jan; Jüni, Peter; Vranckx, Pascal; Ozaki, Yukio; Morice, Marie-Claude; Chevalier, Bernard; Onuma, Yoshinobu; Windecker, Stephan; Tonino, Pim A.L.; Roffi, Marco; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The optimal duration of antiplatelet therapy (APT) in patients at high bleeding risk with or without oral anticoagulation (OAC) after coronary stenting remains unclear. Methods: In the investigator-initiated, randomize, open-label MASTER DAPT trial (Management of High Bleeding Risk Patients Post Bioresorbable Polymer Coated Stent Implantation With an Abbreviated Versus Standard DAPT Regimen), 4579 patients at high bleeding risk were randomized after 1-month dual APT to abbreviated or nonabbreviated APT strategies. Randomization was stratified by concomitant OAC indication. In this subgroup analysis, we report outcomes of populations with or without an OAC indication. In the population with an OAC indication, patients changed immediately to single APT for 5 months (abbreviated regimen) or continued ≥2 months of dual APT and single APT thereafter (nonabbreviated regimen). Patients without an OAC indication changed to single APT for 11 months (abbreviated regimen) or continued ≥5 months of dual APT and single APT thereafter (nonabbreviated regimen). Coprimary outcomes at 335 days after randomization were net adverse clinical outcomes (composite of all-cause death, myocardial infarction, stroke, and Bleeding Academic Research Consortium 3 or 5 bleeding events); major adverse cardiac and cerebral events (all-cause death, myocardial infarction, and stroke); and type 2, 3, or 5 Bleeding Academic Research Consortium bleeding. Results: Net adverse clinical outcomes or major adverse cardiac and cerebral events did not differ with abbreviated versus nonabbreviated APT regimens in patients with OAC indication (n=1666; hazard ratio [HR], 0.83 [95% CI, 0.60–1.15]; and HR, 0.88 [95% CI, 0.60–1.30], respectively) or without OAC indication (n=2913; HR, 1.01 [95% CI, 0.77–1.33]; or HR, 1.06 [95% CI, 0.79–1.44]; P interaction =0.35 and 0.45, respectively). Bleeding Academic Research Consortium 2, 3, or 5 bleeding did not significantly differ in patients with OAC indication (HR, 0.83 [95% CI, 0.62–1.12]) but was lower with abbreviated APT in patients without OAC indication (HR, 0.55 [95% CI, 0.41–0.74]; P interaction =0.057). The difference in bleeding in patients without OAC indication was driven mainly by a reduction in Bleeding Academic Research Consortium 2 bleedings (HR, 0.48 [95% CI, 0.33–0.69]; P interaction =0.021). Conclusions: Rates of net adverse clinical outcomes and major adverse cardiac and cerebral events did not differ with abbreviated APT in patients with high bleeding risk with or without an OAC indication and resulted in lower bleeding rates in patients without an OAC indication. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03023020.